Suitability of non-metallic products for use in contact with water intended for human consumption with regard to their effect on the quality of the water. Methods of test. Taste of water. Method of testing tastes imparted to water by hoses for conveying water for food and drink preparation Part 2.2.3, (29th June 1990) - British Standards Institution,
No abstract available